أثر قاعدة (العادة محكَّمة) في القانون المدني العراقي وتطبيقاتها دراسة تحليلية = The effect and applications of the legal maxim “Custom is an arbitrator” in Iraqi civil law: an analytical study - Ismael, Ardawan Mustafa; Arif, Arif Ali (IIUM Press, International Islamic University Malaysia, 2020)
تعد القواعد الفقهية جزءًا رصينًا من الفقه الإسلامي؛ ذلك أن تلك القواعد تجمع شتات المسائل الفقهية، في أبوابٍ مختلفةٍ، وموضوعاتٍ متشعبة، فترد الجزئيات إلى الكليات، والفروع إلى الأصول. من هنا، فإن البحث سعى إلى استجلاء أثر القاعدة الفقهية الكبرى (العادة محكمة) في القانون المدني العراقي، وذلك باستخدام المنهج الاستقرائي والتحليلي الوصفي. وقد جلّى البحث أن هاته القاعدة أثرت في القانون المدني العراقي تأثيرًا عميقًا؛ ذلك أنها وردت منصوصًا عليها في القانون، وكذلك القواعد المتفرعة عنها. ثم، استعرض البحث أبرز مواد القانون المدني العراقي التي هي تطبيقاتٌ للقاعدة الكبرى والقواعد المتفرعة عنها، لاسيما في البيع والإجارة والمساقاة وعقد العمل. وقد خلُص البحث إلى أن القواعد الفقهية أثْرت القانون المدني العراقي وجعلته قويمًا في صياغته وموادّه. ويوصي البحث، المقنينين وأصحاب القرار، في العالم الإسلامي، العودة إلى ينبوع القواعد الفقهية، والاستفادة منها في تقنين القوانين، في شتى حلائب الحياة. ******************************************************************************* The legal maxims are an integral part of Islamic jurisprudence. These maxims combine the various issues of jurisprudence, from different sections anddiverse topics, so that the particulars (al-juz’iyyāt) are referred to the universals (al-kulliyyāt) and the branches (al-furūʿ) to the basic principles (al-uṣūl). Hence, the research seeks to clarify the impact of a major Islamic legal maxim which is “Custom is an arbitrator” in the Iraqi civil law, using the inductive, analytical and descriptive methods. The research has shown that since this maxim and other maxims branching from it have been mentioned and referred to in the law, these maxims therefore have profoundly affected Iraqi civil law. Then, the study reviews the most prominent articles of the Iraqi civil law which are applications of this major maxim and its subsidiary maxims, especially in the selling and buying, lease, sharecropping contract and work contract. The research concludes that the Islamic legal maxim “Custom is an arbitrator” and its subsidiary maxims influenced the Iraqi civil law and made it strong in its formulation and articles. This research recommends the codifiers and decision-makers of the Islamic world to return to the wellspring of Islamic legal maxims and use them in codifying laws in various spheres of life.